THE IMPORTANCE OF THE ISSUE OF INVESTMENT ATTRACTIVENESS IN ENSURING THE FINANCIAL STABILITY OF REGIONS - Sunatullayeva Shahnoza Khurshid qizi (Web of Journals Publishing, 2025)
Investment attractiveness is one of the chief determinants of regional financial stability. Regions that successfully attract sustainable, diversified, and recurring investment enjoy superior fiscal revenues, job creation, technology transfer, and infrastructure development. This paper takes into account the mechanisms whereby investment attractiveness contributes to regional financial resilience, the most important determinants of attractiveness, measurement approaches, and policy measures for strengthening investment flows while mitigating risks. Emphasis is placed on balancing short-term capital mobility with long-run economic sustainability and social justice.
Keywords: Investment attractiveness, financial stability, regional, development, foreign and domestic investment, public-private partnerships, risk management